Экономика управления предприятием: учебное пособие - Верховская М. В. Марина Витальевна; Меньшикова Е. В. Екатерина Валентиновна; Древаль А. Н. Анатолий Николаевич (Томск, Изд-во ТПУ, 2019)
Заглавие с титульного экрана